2020
DOI: 10.1007/s00198-020-05594-8
|View full text |Cite
|
Sign up to set email alerts
|

Fracture prediction from FRAX for Canadian ethnic groups: a registry-based cohort study

Abstract: Purpose-FRAX ® is calibrated using population-specific fracture and mortality data. The need for FRAX to accommodate ethnic diversity within a country is uncertain. We addressed this question using the population-based Manitoba Bone Mineral Density (BMD) Program registry and self-reported ethnicity.Methods-The study population was women age 40 years or older with baseline FRAX assessments (Canadian and other ethnic calculators), fracture outcomes and self-reported ethnicity (White N=68,907 [referent], Asian N=… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 30 publications
(30 reference statements)
0
11
0
1
Order By: Relevance
“…By analysing the Canadian population-based Manitoba bone mineral density (BMD) Program registry data, in 2021 Leslie et al (8) reported a study that included 68,907 Caucasian women (mean age: 64.7±10.9 years) and 1,910 Asian women (mostly Chinese and Filipino, mean age: 62.8±9.9 years). During a follow-up period of 8.8±5.1 years for Caucasians and 6.5±5.0 years for Asians, incident hip fracture rate per 1,000 person-years was 0.6 [95% confidence interval (CI): 0.2-1.0] for Asians and 3.6 (95% CI: 3.5-3.8) for Caucasians (Asian vs. Caucasian ratio: 0.17).…”
Section: Hip Fragility Fracturementioning
confidence: 99%
See 1 more Smart Citation
“…By analysing the Canadian population-based Manitoba bone mineral density (BMD) Program registry data, in 2021 Leslie et al (8) reported a study that included 68,907 Caucasian women (mean age: 64.7±10.9 years) and 1,910 Asian women (mostly Chinese and Filipino, mean age: 62.8±9.9 years). During a follow-up period of 8.8±5.1 years for Caucasians and 6.5±5.0 years for Asians, incident hip fracture rate per 1,000 person-years was 0.6 [95% confidence interval (CI): 0.2-1.0] for Asians and 3.6 (95% CI: 3.5-3.8) for Caucasians (Asian vs. Caucasian ratio: 0.17).…”
Section: Hip Fragility Fracturementioning
confidence: 99%
“…In 2021, by analysing the above-mentioned Manitoba BMD Program registry data, Leslie et al (8) reported that, at baseline prior fracture history was recorded in 20.1% of the Caucasian women (total included n=68,907, mean age: 64.7±10.9 years) and 11.7% of the Asian women (total: n=1,910, mostly Chinese and Filipino, mean age: 62.8±9.9 years). During the follow-up of 8.8±5.1 years for Caucasians and 6.5±5.0 years for Asians, the incident rate for major osteoporotic fracture (MOF; a composite of hip, humerus, forearm, and clinical vertebral fractures) per 1,000 person-years was 11.4 (95% CI: 11.2-11.7) for Caucasians and 5.0 (95% CI: 3.8-6.2) for Asians.…”
Section: General Fragility Fracturesmentioning
confidence: 99%
“…It is widely acknowledged that the application of FRAX® should be country-specific. However, as FRAX® has progressively become more widely utilized globally, it was realized that the use of FRAX® not only should be ethics-specific 27 but also should be disease-specific 28 30 when applied in precision medicine. As previously mentioned, RA has been incorporated as a dichotomous predictor in the FRAX®; however, no RA-specific guidelines or recommendations, as of GIOP, 13 , 14 based on FRAX® are available currently.…”
Section: Discussionmentioning
confidence: 99%
“…The principle presented here can also apply to osteoporosis in men and other BMD measure sites such as the lumbar spine. In recent Canadian studies, it is noted that East Asians are more likely to be diagnosed with osteoporosis based on BMD (6,8).…”
mentioning
confidence: 99%